Screening for urine abnormalities among preschool children in western Saudi Arabia - Alharthi, Abdulla A.; Taha, Azza A.; Edrees, Awatif E.; Elnawawy, Ali N.; Abdelrahman, Azza H. A (Saudi Medical Journal, 2014)
OBJECTIVES: To estimate the frequency of urinary problems among preschool children.METHODS: In this cross-sectional study, 1000 preschool asymptomatic children attending the outpatient clinics of the Children’s Hospital, Taif, Kingdom of Saudi Arabia between August 2013 and December 2013 were subjected to dipstick urine analysis. Microscopic examination was performed for the abnormal dipstick samples, and children with hematuria were investigated for kidney function.RESULTS: Dipstick urine analysis revealed abnormal findings in 25.1% of the screened children. The most common dipstick abnormalities were positive nitrite test in 18.1%, hematuria in 16.9%, and positive leukocyte esterase test in 14.3% of the cases. The most common abnormality in microscopic urine examination was crystals in 13% of the cases. Pyuria were evident in 5% of cases and hematuria in 2.5%. The most common bacteria in positive urine culture samples was Escherichia coli in 62.6%.CONCLUSION: In view of these important findings, dipstick screening should be implemented in preschool children.